Decifrando a proveniência dos folhelhos da formação Ponta Grossa na região de Rio Verde de Mato Grosso e Coxim (MS) através de métodos petrográficos e geoquímicos - Montibeller, Cibele Carolina [UNESP]; Zanardo, Antenor [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
In the region of Rio Verde de Mato Grosso and Coxim (State of Mato Grosso do Sul, Brazil) Devonian sedimentary rocks related to the Ponta Grossa Formation occur. In this region, the Ponta Grossa Formation outcrops consist on a sequence of gray to black shales and siltstones, with levels of cream, green and reddish clayey siltstones overlain by very fine feldspathic and micaceous sandstones. Weakly structured, yellow clayey siltstones occur above the sandstones. Chemically, these pelitic levels are classified as mature shales/mudstones, derived mainly from intermediate and/or mafic igneous rocks. Diagrams used for provenance and tectonic setting discrimination revealed that these Ponta Grossa Formation sediments may have more than one origin, as they can be classified as deposited in passive or active margins. However, given the tectonic setting of the Paraná Basin during the Devonian, the source of these sediments is likely to be rocks formed in active margins (magmatic arcs), which were eroded and the resulting sediments deposited in passive margins (intracratonic basin).
Deciphering the provenance of the Ponta Grossa formation shales in the region of Rio Verde de Mato Grosso and Coxim (State of Mato Grosso, Brazil) using petrographic and geochemical methods
Keywords: Devonian; Lithogeochemistry; Paraná basin